Nilai-Nilai dan Kearifan Lokal Suku Makassar Sebagai Sumber Pendidikan Ekonomi Informal dalam Keluarga - Yani M; Muhammad Hasan; Tuti Supatminingsih (FKIP Universitas Lampung, 2021)
Local wisdom is an order of life values inherited from the previous generation to the next generation in the form of religion or religion, culture and customs in oral form in the social system of society. One of the local cultural wisdom of the Makassar tribe is the principle of life adopted by the people. The principle of life is the guide of people's lives in shaping their human character. This study aims to examine the principle of the life of the Makassar tribe, which is a source of informal economic education in the Family. The research method used is a descriptive qualitative research method in literature study with data sources coming from books or existing literature. The meaning of the Makassarese principle of life can be used as a source of informal economic education in the Family. The principle of the life of the Makassar tribe, which is the source of Informal Economic Education in the Family, includes: (1) the principle of not surrendering to circumstances; (2) solidarity and togetherness, and (3) self-esteem. Keywords: Local values, local wisdom, informal economic education, family